Vascular inflammation in patients with obstructive sleep apnoea and coronary artery disease shown on coronary computed tomography angiography attenuation. (4th February 2022) - Yuvaraj, J; Cameron, W; Andrews, J; Lin, A; Nerlekar, N; Nicholls, S J; Hamilton, G; Issa, M; Che, Z C; Lim, E; Wong, D T L
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Obstructive sleep apnoea (OSA) is associated with increased plaque burden in coronary artery disease (CAD), but the role of vascular inflammation in this relationship is unclear. Coronary computed tomography angiography (CTA) enables surrogate assessment of systemic inflammation via subcutaneous adipose tissue attenuation (ScAT-a), and of coronary inflammation via epicardial adipose tissue volume and attenuation (EAT-v and EAT-a) and pericoronary adipose tissue attenuation (PCAT-a). Purpose: To investigate whether vascular inflammation is increased in patients with severe OSA and high plaque burden. Methods: Patients with clinically indicated polysomnography and coronary CTA were included. Severe OSA was classified as apnoea/hypopnoea index (AHI) >30. High plaque burden was defined as a CT-Leaman score (CT-LeSc) >8.3. Patients with both severe OSA and high plaque burden were defined as 'Group 1', all other patients were classified as 'Group 2'. ScAT-a, EAT-a, EAT-v and PCAT-a were assessed on semi-automated software. Results: A total of 91 patients were studied (59.3 ± 11.1 years). Severe OSA was associated with high plaque burden (p = 0.02). AHI correlated with CT-LeSc (r = 0.24, p = 0.023). Group 1 had lower EAT-a and PCAT-a compared to Group 2 (EAT-a: -87.6 vs. -84.0 HU, p = 0.01; PCAT-a: -90.4 vs. -83.4 HU, p < 0.01). However, among patients without high plaque burden, EAT-a was increased in patients with severe OSA versus mild-moderate OSA (-80.3 vs. -84.0 HU, p = 0.020). On multivariable analysis, EAT-a independently associated with severe OSA and high plaque burden (p < 0.02), and PCAT-a associated with severe OSA and high plaque burden, and hypertension (all p < 0.01). Conclusions: EAT attenuation is decreased in patients with severe OSA and high plaque burden but increased in patients with severe OSA and low plaque burden. These divergent results suggest coronary inflammation may be increased in OSA independent of CAD, but larger studies are required to validate these findings.